Development of mathematical cost model for preheated end-milling of AISI D2 tool steel - El-hadie, Mohamed; Karim, A.N. Mustafizul; Amin, A. K. M. Nurul; Lajis, M. A. (IEOM Research Solutions Pty Ltd, 2011)
Mohamed Elhadie1, A. N. Mustafizul Karim1, A. K. M. Nurul Amin1 Department of Manufacturing and Materials Engineering International Islamic University Malaysia, Gombak, Kuala Lumpur 53100, Malaysia M. A. Lajis2 Faculty of Mechanical and Manufacturing Engineering Universiti Tun Hussein Onn Malaysia, Batu Pahat, Johor Bahru 86400, Malaysia Abstract In this research paper, reliable mathematical model for estimating the cost of preheated end-milling of AISI D2 tool steel using TiAlN coated carbide tool inserts is developed. Initially, the different components of machining cost were identified, followed by establishment of equations to determine their values. Then, the required experimental and non-experimental data were collected and the bottom-up approach was adopted for evaluating the cost of machining corresponding to each of fifteen experimental runs. The Response Surface Methodology (RSM) was used to develop the model in which the cost of machining is given as a function of the machining parameters; cutting speed, feed per tooth, and preheating temperature, and expressed in RM per cm3. ANOVA output was utilized to check the adequacy of the developed model. The developed model was found to be statistically adequate and this was confirmed by the small prediction errors made by the model. Keywords: machining